4-PBA prevents pressure overload-induced myocardial hypertrophy and interstitial fibrosis by attenuating endoplasmic reticulum stress. (5th December 2015) - Luo, Tao; Chen, Baihe; Wang, Xianbao
Abstract: Our previous study indicated that attenuation of endoplasmic reticulum (ER) stress by administration of 4-phenylbutyric acid (4-PBA) could prevent cardiac rupture and remodeling in a mouse model of myocardial infarction (MI). However, whether 4-PBA is protective in hypertrophic heart disease is unclear. Thus, we tested the therapeutic effect of 4-PBA on pressure-overload induced myocardial hypertrophy. Transverse aortic constriction (TAC) was used to create myocardial hypertrophy in C57BL/6 male mice for 4 weeks. Immediately after surgery, the mice were administrated either 4-PBA (20 mg/kg/day) or 0.9% NaCl by intraperitoneal injection. At the end of 4 weeks, the mice underwent high-resolution echocardiographic imaging. Our results showed that both the left ventricular posterior wall thickness at end systole (LVPWs) and diastole (LVPWd) were increased in the TAC group, compared to control. 4-PBA administration attenuated hypertrophy and decreased the heart weight over body weight ratio. Masson's trichrome staining showed that myocardial interstitial fibrosis and collagen deposition were also decreased by 4-PBA. We next detected the ER stress response in the heart tissues of TAC mice in different time points. Western blotting showed that the expression of ER stress marker, GRP78, CHOP and phosphor-PERK, were persistently increased 4 weeks after TAC. The treatment of 4-PBA inhibited the expression of ER stress markers. We also demonstrated that the 4-PBA at 20 mg/kg/day had no effect on histone 3 deacetylation inhibition, while attenuating ER stress and TAC-induced hypertrophy. These findings suggest that 4-PBA may be a therapeutic strategy to consider in preventing pressure-overload induced myocardial hypertrophy and interstitial fibrosis by selectively attenuating ER stress. Highlights: Endoplasmic reticulum (ER) stress response persists in the pathogenesis of myocardial hypertrophy. 4-PBA ameliorates pressure-overload induced myocardial hypertrophy. 4-PBA inhibits pressure-overload induced myocardial interstitial fibrosis.